Association between sleep disorders and osteoarthritis: A case–control study of 351, 932 adults in the UK. (28th April 2021) - Jacob, Louis; Smith, Lee; Konrad, Marcel; Kostev, Karel
Summary: This study aimed to analyse the association between sleep disorders and osteoarthritis in adults in the UK. This case–control study included patients aged ≥ 18 years who were diagnosed with osteoarthritis for the first time in one of 256 general practices in the UK between 1997 and 2016 (index date). Patients without osteoarthritis were matched (1:1) to those with osteoarthritis by sex, age, index year, general practice, observation time prior to index date (in years), obesity, injuries, and other types of arthritis. For patients without osteoarthritis, the index date was a randomly selected visit date between 1997 and 2016. The presence of sleep disorders prior to index date was assessed in the two groups. Finally, conditional logistic regression analyses were conducted to investigate the association between sleep disorders and osteoarthritis. This case–control study included 351, 932 adults (61.5% women; mean [ SD ] age 64.9 [14.2] years). Overall, there was a significant association between sleep disorders and osteoarthritis (odds ratio = 1.25, 95% confidence interval = 1.22–1.29). This finding was corroborated in all sex and age subgroups, except in patients aged > 80 years. In terms of the type of sleep disorder, non‐organic sleep disorders, hypersomnia and sleep apnea were associated to a significant extent with higher odds of developing osteoarthritis. Finally, the relationship between sleep disorders and osteoarthritis was significant in all osteoarthritis subgroups, except in that of patients with knee osteoarthritis. Based on these results, it can be concluded that sleep disorders may play a role in the development of osteoarthritis.